Optimalisasi Hasil Belajar Siswa Melalui Metode Jigsaw Dengan Media Quizizz Di Kelas XI APHP SMKN 2 Sukoharjo - Wandhani, Fatonah Isnaini; Niken Tari, Agustina Intan; Marlina, Iin (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2025)
This study aims to improve student learning outcomes through the application of the cooperative learning model type Jigsaw combined with the use of the Quizizz application as an interactive medium. The research subjects were 26 students of class XI Agribusiness of Agricultural Product Processing (APHP) at SMKN 2 Sukoharjo. The research method used was Classroom Action Research (CAR) based on the Kemmis & McTaggart model, consisting of two cycles. The research instruments included learning outcome tests, observation sheets, and documentation. The results showed an increase in mastery learning from 38.5% in the initial condition to 57.7% in the first cycle, and further increased to 73.1% in the second cycle. The implementation of the Jigsaw method integrated with Quizizz proved effective in enhancing students' academic achievement and active participation. Keywords: Jigsaw, Quizizz, learning outcomes, cooperative learning